A SEMIOTIC APPROACH ON INDONESIAN MEGALITHS STUDY - Tular Sudarmadi (Humaniora, 1999)
Megalithic structures in Indonesia have their own unique characteristics, compared with elsewhere, because of the influences of Indian, Arabic, and European cultures, as well as local developments . They exhibit great variation in shape, size and degree of complexity. Perry (1918), Hoop (1935), Geldern (1945), Heekeren (1958) and Soejono (1984) have identified stone tables (dolmen), slabs, coffins, menhirs, enclosures (watu kandang/- watu temu gelang), statues, pits (batu dakon), paved paths, upright statues, terraced platforms, jars, seats, elliptical coffins, rectangular coffins, chamber graves, cubic coffins (waruga), vat coffins and thrones (pelinggih) . Geldern (1945, p . 149) concluded that there were two main waves of megalithic culture in Indonesia . He connected the first wave, during the Neolithic period from 2500 to 1500 BC with Austronesian speakers, who utilized the quadrangular adze . These people constructed megalithic tables, menhir, terraced platforms, pits, and seats . The second wave, during the Bronze-Iron period from 300 to 100 BC, produced slab, elliptical, cubic and rectangular coffins, chamber graves and statues. While accepting Heine- Geldern's basic hypothesis, later researchers suggested that the two main waves of megalithic culture became intermingled and developed local variations (Heekeren 1958, p . 44) .